Efficacy of Neem Leaf and Seed Powder in Teabag to Control Sitophilus oryzae on Rice - Aflah, Nurul; Afriana, Hafidhah; Husni, Husni; Chamzurni, Tjut; Jauharlina, J (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2021)
Neem (Azadirachta indica Juss) powder is often used as a botanical insecticide which is applied directly to stored rice to control the rice beetle (Sitophilus oryzae), however this method may cause contamination on the stored rice. This study aimed to determine the effectiveness of neem leaf and seed powder in teabag packaging in controlling S. oryzae. The study used a completely randomized design with a factorial pattern consisting of 2 treatment factors. The first factor was the type of neem powder (without powder, leaf powder, and seed powder), and the second factor was the application technique (direct sow and in teabag packaging). The results showed that the type of neem powder and its application technique on rice interacted significantly in causing mortality of S. oryzae at 2 - 3 days after treatment (DAT) and was very significant at observations of 4-7 DAT. Applying leaf and seed powder in teabag packaging can provide higher yields than direct sowing. At 7 DAT, the highest mortality of S. oryzae occurred in the treatment of neem seed powder with direct sow application technique (57.50%), the mortality was lower in tea packaging (33.33%). The application of neem powder in teabag packaging caused a higher number of the adult of the first offspring of S. oryzae and the damage to rice. The application of leaf and seed powder of neem in teabag packaging does not cause contamination of rice, so it is safer for consumers.